Nutritional status, glycaemic control and barriers to treatment compliance among patients with type 2 diabetes attending public primary health clinics in Maseru, Lesotho. Issue 3 (2nd September 2019) - van den Berg, Louise; Mokhehle, Mohlakotsana; Raubenheimer, Jacques
Abstract : Objectives: To evaluate the nutritional status, glycaemic control and barriers to treatment compliance of outpatients with type 2 diabetes mellitus (T2DM) attending two public primary health clinics in Maseru, Lesotho. Design : Cross-sectional analytical study. Setting: Lesotho Defence Force Clinic and Domiciliary Clinic. Subjects : 124 participants with T2DM, 30–69 years. Outcome measures : Sociodemography, medical history, diet, lifestyle, metabolic risk-related anthropometry, glycaemic and metabolic control, and barriers that may impact on treatment compliance. Results: Participants (53.9; SD 9.4 years; 79.5% females; 53.3% diagnosed for > 5 years) were knowledgeable about basic lifestyle recommendations for diabetes, and reported being active (98.3%). However, 88.5% were overweight or obese; 93.4%, 78.1%; 66.1% did not meet the recommended intakes of dairy, vegetables and fruit; 10.7% used tobacco; and 52% of men drank excessively. None performed blood glucose self-monitoring, and 90.2% were ignorant of normal blood glucose ranges, while 94.3% had uncontrolled hypertension despite being on anti-hypertensive medication. Participants were rarely screened for long-term glycaemic control or comorbidities, or referred to dietitians, but 98.4% were satisfied with the services. Conclusions: In this setting, patients were not meeting treatment goals for T2DM, and were not being screened or referred, rendering clinic visits a revolving door that poses the risk of costly complications.